Synergistic Amelioration of Arthritis in Preclinical Models through Azathioprine and Pioglitazone Combination Therapy - Pratap, Veeresh Babu; Varla, Soundarya; M., Ganga Raju (Advanced Concepts in Pharmaceutical Research Vol. 9, 2024)
The current investigation aimed to explore the antioxidant and anti-arthritic properties of a combination therapy involving azathioprine and pioglitazone, compared to their individual use, in rodent models. The antioxidant potential of the drugs and their combination were assessed through tests for scavenging activities against H2O2 and nitric oxide. Furthermore, their anti-arthritic effects were evaluated using both in vitro methods such as protein denaturation and membrane stabilization assays, and in vivo models including formaldehyde and complete Freund’s adjuvant (CFA)-induced arthritis. Results indicated that the combined treatment exhibited superior scavenging of free radicals compared to the individual drugs, suggesting enhanced antioxidant activity. Moreover, the combination showed significant inhibition of protein denaturation and red blood cell proliferation in vitro. In animal models, it effectively reduced paw volume in both formaldehyde and CFA-induced arthritis, along with normalization of altered biochemical parameters, as confirmed by radiological and histopathological analyses. These findings highlight the synergistic interaction between azathioprine and pioglitazone, leading to enhanced antioxidant and anti-arthritic effects compared to their individual administration.